Conflict and Conflict Resolution in the pre-Islamic Arab Society - Kirazli, Sadik (Islamic Studies, 2011)
This study aims to establish a background in order to understand the conflict resolution approaches and methods of Prophet Mu╒ammad (peace be on him). In Islamic chronology, there are two very distinct historical periods: the pre-Islamic and the Islamic periods. It is apparent that the attitude of the Prophet, who grew up in the pre-Islamic era prior to his appearance as the Messenger of God in the Arabian Peninsula, towards the existing Arab customs and their usage in the Islamic period varies from outright rejection to adaptations and modifications on different levels. This deduces a somewhat continuity between the pre-Islamic conflict resolution methods and principles in dealing with conflict into Islamic times. So, the conflict resolution skills and principles that the Prophet had utilized in the pre-Islamic period would most likely serve as potential reference and sources in his future conflict intervention efforts.